Climate change Lake Victoria Region - Adam, Rahma (WorldFish, 2024)
This documentary is about climate change, gender and livelihoods among fisher communities in the Lake Victoria Zone Region in Kenya. The video depicts the views of women and men in Migori and Homabay counties, with regards to challenges and opportunities they see as they are involved in the fish value chain (e.g., fishing, selling of fish, boat making and repairing, among others). They report on the impacts of climate change in their livelihoods, issues of access to finance and much more. Moreover, the video shows the views and recommendations of researchers, government agencies, development actors on how to better the lives of fisher communities in the two counties in Kenya.